Answer:
(7,3)
Step-by-step explanation:
you can add the equations together to eliminate y and first solve for x
(x-3y = -2) + (x+3y=16) = (2x = 14)
x = 7
then plug x into one of the equations to solve for y
(7) - 3y = -2
9 = 3y
y = 3
the solution is (7,3)
Answer: (7, 3)
Step-by-step explanation:
x - 3y = -2
x + 3y = 16
Here we can add the two equations together to cancel out the y
2x = 14
divide by 2 on both sides to get
x = 7
Now that we have the X value, plug in x value into an equation to get the Y
x - 3y = -2
7 - 3y = -2
-3y = -9
y = 3
So the solution is (7, 3)